2014
DOI: 10.1371/journal.pntd.0003122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Japanese Encephalitis Virus in Mosquitoes in Taiwan during 2005–2012

Abstract: Japanese encephalitis (JE) is a mosquito-borne zoonotic disease caused by the Japanese encephalitis virus (JEV). Pigs and water birds are the main amplifying and maintenance hosts of the virus. In this study, we conducted a JEV survey in mosquitoes captured in pig farms and water bird wetland habitats in Taiwan during 2005 to 2012. A total of 102,633 mosquitoes were collected. Culex tritaeniorhynchus was the most common mosquito species found in the pig farms and wetlands. Among the 26 mosquito species collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 26 publications
3
69
0
Order By: Relevance
“…From the isolation of the prototype strain of JEV in 1935 until recently, most of the circulating strains of JEV belonged to g3 and were at the origin of major epidemics in Southeast Asian countries (5). Recently, a shift in prevalence from JEV g3 to g1 has been observed in several Asian countries (6)(7)(8), while some strains of JEV g5 have been occasionally isolated in China in 2009 (9) and in South Korea in 2010 (10). The JEV g5 prototype strain, strain Muar, was originally isolated in 1952 from an encephalitis patient in Malaysia (11) and was found to be genetically and serologically distinct from other genotypes (12)(13)(14).…”
mentioning
confidence: 99%
“…From the isolation of the prototype strain of JEV in 1935 until recently, most of the circulating strains of JEV belonged to g3 and were at the origin of major epidemics in Southeast Asian countries (5). Recently, a shift in prevalence from JEV g3 to g1 has been observed in several Asian countries (6)(7)(8), while some strains of JEV g5 have been occasionally isolated in China in 2009 (9) and in South Korea in 2010 (10). The JEV g5 prototype strain, strain Muar, was originally isolated in 1952 from an encephalitis patient in Malaysia (11) and was found to be genetically and serologically distinct from other genotypes (12)(13)(14).…”
mentioning
confidence: 99%
“…7,19 Another possible reason is that there has been a dramatic shift in the dominant genotype of the JEV from GIII to GI circulating in Taiwan over the past two decades. 15,20,21 It has been found that antibodies elicited by JE-VAX (Nakayama strain) among Taiwanese children show reduced neutralizing potency against the genotype of the emerging GI JEV strain. 22 Taiwan has been using an inactivated mouse brain Nakayama-NIH vaccine strain since 1968, except for the brief use of an inactivated freeze-dried Beijing vaccine strain in 1988.…”
Section: Discussionmentioning
confidence: 99%
“…These provide suitable environments for maintaining the JEV infection cycle. 16,27 2) In Taiwan, almost all DF cases (approximately > 95%) over the last decade occurred in the southern region of Taiwan. 6,7 This fact and the high proportion of JE cases suggest that mosquitoes and the JE virus are well adapted to this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations